Approved indications and other possible utilizations of anti-TNFa biologic drugs - C. Montecucco; W. Grassi (PAGEPress Publications, 2011)
The article describes the EMEA approved indications of TNFa antagonists (adalimumab, etanercept and infliximab) in the various clinical conditions and their increasing use in diseases other than those already approved. The Authors discuss their use during pregnancy, the efficacy of a second TNFa antagonist after failure or side effects development with a previous biologic agent and the different efficacy of the various agents depending on the different clinical conditions.